Targeting Indoleamine 2,3-Dioxygenase 1: Fighting Cancers via Dormancy Regulation - Yang, Chao; Ng, Chan-Tat; Li, Dan; Zhang, Lei (Frontiers in Immunology, 2021)
Indoleamine 2,3-Dioxygenase 1 (IDO1)-mediated dormancy represents a quiescent state of tumour cells, and it has been consistently linked to metastasis and cancer recurrence. However, despite its pivotal role in cancer development and progression, its underlying mechanisms are still elusive and are worth pursuing. In this review, we summarised the IDO1 pathways contributing to dormancy. Critically, the sources of IDO1 activity were found to be distinct between the initiation and maintenance stages. Furthermore, factors other than the well-studied IDO1/kynurenine/aryl hydrocarbon receptor axis were identified to be involved in dormancy. We also discussed different strategies for cancer treatment via regulating IDO1-dependent dormancy and suggested nanotechnology as a potentially effective treatment delivery system.